2023
DOI: 10.1039/d3cc00693j
|View full text |Cite
|
Sign up to set email alerts
|

Remote electronic effect on the N-heterocyclic carbene-catalyzed asymmetric intramolecular Stetter reaction and structural revision of products

Abstract: The remote electronic effects of chiral N-heterocyclic carbene catalysts on the asymmetric intramolecular Stetter reaction are investigated. The reaction rate and enantioselectivity were markedly influenced by a substituent at a...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 48 publications
2
6
0
Order By: Relevance
“…The remote electron‐withdrawing substituents were also beneficial to prevent racemization of highly enolizable products. The results are consistent with the two conclusions that the rate‐limiting step with triazolinylidene NHC is interchangeable as in the reaction with thiazolinylidene, [5] and that the remote electronic effect is operative as we previously proposed [43–45,49] . DFT calculations and NCI analysis confirmed that the origin of the enantioselectivity is the orientation of the aldehyde aryl group with respect to the diaminoenol aryl group in the C−C bond forming TS as proposed in the literature.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…The remote electron‐withdrawing substituents were also beneficial to prevent racemization of highly enolizable products. The results are consistent with the two conclusions that the rate‐limiting step with triazolinylidene NHC is interchangeable as in the reaction with thiazolinylidene, [5] and that the remote electronic effect is operative as we previously proposed [43–45,49] . DFT calculations and NCI analysis confirmed that the origin of the enantioselectivity is the orientation of the aldehyde aryl group with respect to the diaminoenol aryl group in the C−C bond forming TS as proposed in the literature.…”
Section: Discussionsupporting
confidence: 91%
“…The results are consistent with the two conclusions that the rate-limiting step with triazolinylidene NHC is interchangeable as in the reaction with thiazolinylidene, [5] and that the remote electronic effect is operative as we previously proposed. [43][44][45]49] DFT calculations and NCI analysis confirmed that the origin of the enantioselectivity is the orientation of the aldehyde aryl group with respect to the diaminoenol aryl group in the CÀ C bond forming TS as proposed in the literature. Moreover, the distortion/interaction analysis suggested that the distortion of the diaminoenol intermediate moieties of the TS caused by the remote electron-withdrawing substituents could be responsible for the increased enantioselectivity.…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…We investigated the performance of the series of NHCs bearing variable remote substituents in an intramolecular Stetter reaction of α,β‐unsaturated esters 21 (Table 4). [13d] When α,β‐unsaturated ester 21a was subjected to the reaction with 1b and proton sponge in 1,2‐dichloroethane at 0 °C for 100 min, cyclized product 22a was produced in 53 % yield with 96 % ee (entry 2). After investigating NHCs with various substituents at the indane ring, we found that the more electron‐deficient NHC provided better conversion (entries 1–5).…”
Section: The Remote Electronic Effect On the Nhc‐catalyzed Umpolung R...mentioning
confidence: 99%